Online mindfulness interventions in the care of people with physical and mental health conditions: a scoping review - Susan Jaglal; Sarah Munce; Robert Simpson; Catharine Craven; Laure Perrier; Vjura Senthilnathan; Susan Zahir; Mary-Jo Fetterly (BMJ Open)
Objective With growing access to the internet, online mindfulness programmes have become more commonly used to manage physical and mental health conditions. This scoping review aims to determine the nature and extent of the literature, and key characteristics, of online mindfulness-based interventions (MBIs) for adults with physical or mental health conditions.Design A scoping review guided by the Joanna Briggs Institute framework.Data sources MEDLINE, CINAHL, Embase, PsycINFO, Allied and Complementary Medicine and the Cochrane Central Register of Controlled Trials.Eligibility criteria Studies focusing on online MBIs, online mindfulness-based stress reduction and online mindfulness-based cognitive therapy (MBCT) in adults with a physical or mental health condition were included.Data extraction and synthesis Study and participant characteristics, key intervention characteristics, outcome measures and results were abstracted.Results 84 studies were included. Online MBIs have been studied in many different physical and mental health conditions; however, 63 of the included studies were for physical health conditions. MBCT was the most common intervention type assessed, with 33 of the included studies assessing it. Regarding intervention characteristics, intervention duration was similar across intervention type at 8 weeks, with sessions led by therapists, clinicians or mindfulness instructors. Web-based and videoconferencing were the most common delivery formats. Intervention content generally remained similar to standardised MBIs, with the addition of psychoeducation and disease management. Many studies did not report on tailoring the intervention to the participant population. There was a lack of consistency in reporting intervention characteristics.Conclusions This review highlights some evidence for online mindfulness programmes for both physical and mental health conditions. However, intervention componentry remains somewhat obscure, and reporting on tailoring appears relatively sparse. Greater consistency in reporting intervention componentry will improve knowledge and study in this area and enhance the translation of these interventions to clinical settings.